It is just knowing what the argument is, and multiplying two things together.
\(\displaystyle z_1\cdot z_2 = |z_1|e^{i\text{Arg}(z_1)}\cdot |z_2|e^{i\text{Arg}(z_2)} = |z_1\cdot z_2| e^{i(\text{Arg}(z_1)+\text{Arg}(z_2))}\)
I think using z = r exp(i theta) is kind of like cheating. (OK, OK, It's not, but I just don't like it.)
I like this better:
Prove arg(z1*z2)=arg z1+arg z2
IF z1 = r1 (cos t1 + i sin t1)
and z2 = r2 (cos t2 + i sin t2)
then z1 z2 = r1 r2(cos t1 cos t2 - sin t1 sin t2 + i(cos t1 sin t2 + cos t2 sin t1))
= r1 r2(cos (t1 + t2) + i sin(t1 + t2))
using your well-known sum identities.
So arg(z1 z2) = t1 + t2
etc.
This site uses cookies to help personalise content, tailor your experience and to keep you logged in if you register.
By continuing to use this site, you are consenting to our use of cookies.